2019
DOI: 10.1021/acs.langmuir.8b04252
|View full text |Cite
|
Sign up to set email alerts
|

Microrheology and Spatial Heterogeneity of Staphylococcus aureus Biofilms Modulated by Hydrodynamic Shear and Biofilm-Degrading Enzymes

Abstract: Particle tracking microrheology was used to investigate the viscoelasticity of Staphylococcus aureus biofilms grown in microfluidic cells at various flow rates and when subjected to biofilm-degrading enzymes. Biofilm viscoelasticity was found to harden as a function of shear rate but soften with increasing height away from the attachment surface in good agreement with previous bulk results. Ripley's K-function was used to quantify the spatial distribution of the bacteria within the biofilm. For all conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In all cases, the flow was laminar (Reynolds number in the range 0.3 to 3.0). Shear stress (τ; in mPa) was calculated with the formula presented in Hart et al 26 as follow: where Q is the flow rate in mL/min, µ is the dynamic viscosity of water at 25 °C (0.89 mPa · s), w and h are the width and height of the flow cell channel respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the flow was laminar (Reynolds number in the range 0.3 to 3.0). Shear stress (τ; in mPa) was calculated with the formula presented in Hart et al 26 as follow: where Q is the flow rate in mL/min, µ is the dynamic viscosity of water at 25 °C (0.89 mPa · s), w and h are the width and height of the flow cell channel respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to test such hypothesis, the biofilms of Chlorella vulgaris were cultivated in flow-cells at several shear stress and their architecture characterized by confocal laser scanning microscopy (CLSM) and image analysis. Advanced microscopy techniques such as fluorescence recovery after photobleaching (FRAP) and particle tracking have been particularly useful in characterizing diffusion and the rheological properties of bacterial biofilms 25 , 26 and were therefore here employed together with an erosion test to determine the physical and cohesion properties of microalgae biofilms as a function of the shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…In order to remove the quadratic behavior of K ( r ) that is characteristic of CSR, the function H ( r ) is often used ( Haase, 1995 ; Hart et al, 2019 ):…”
Section: Resultsmentioning
confidence: 99%
“…External shear flows can also alter the mechanical properties of the biofilm. A study in S. aureus identified that an external shear stress of 1–10 mPa makes the biofilm three times harder than the one grown in static conditions, probably as a response to less favourable attachment conditions [ 92 , 93 ].…”
Section: Mechanical Surface Waves and Fluid Flows Control Biofilm Attmentioning
confidence: 99%